2010
DOI: 10.1063/1.3479397
|View full text |Cite
|
Sign up to set email alerts
|

Unusual photochemical dynamics of a bridged azobenzene derivative

Abstract: In a large-scale simulation study of ultrafast photochemical dynamics for an azobenzene compound with an additional ethylenic bridge we have found unexpected features: while the dynamics starting from the Z isomer follow a barrierless path with steep gradients, the dynamics starting from the E isomer proceed through a different conical intersection surrounded by a rather flat potential energy landscape and then encounter a sizeable barrier in the electronic ground state that markedly influences the reaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
83
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(102 citation statements)
references
References 26 publications
16
83
3
Order By: Relevance
“…One CI was reported to play an important part in nonadiabatic transitions between the two states involved in cis-trans photodynamics processes. 19,21 As can be seen from Figure 5, nonadiabatic transitions in the dynamics starting from 1Z pass through the avoided crossing near CI 1 and CI 2 between S 1 and S 0 states.…”
Section: Z-1e Photoisomerization Dynamicsmentioning
confidence: 95%
See 3 more Smart Citations
“…One CI was reported to play an important part in nonadiabatic transitions between the two states involved in cis-trans photodynamics processes. 19,21 As can be seen from Figure 5, nonadiabatic transitions in the dynamics starting from 1Z pass through the avoided crossing near CI 1 and CI 2 between S 1 and S 0 states.…”
Section: Z-1e Photoisomerization Dynamicsmentioning
confidence: 95%
“…Previous dynamics simulations [19][20][21] demonstrated that one minimum-energy CI plays an important part in nonadiabatic transitions between the two states involved in transcis photodynamics processes. However, in this work, CI 1 and CI 2 were found to be responsible for nonadiabatic transitions during 1E-1Z photoisomerization.…”
Section: B Molecular Dynamics Simulations 1 1e-1z Photoisomerizatiomentioning
confidence: 99%
See 2 more Smart Citations
“…The problem is exacerbated by the necessary treatment of electrons in molecular machines whose motions depend on excited state transition states or the formation of chemical bonds. Nevertheless, such systems have been tackled successfully using ab initio approaches, in molecular switches, 28,29 rotaxanetype molecular shuttles 10,30 and photochemically-driven, artificial cilia. 31 Where conformational properties and the stochastic behavior of molecules are solely responsible for their function, molecular dynamics (MD) 10,20,30,[32][33][34] and molecular mechanics (MM) 31,33,[35][36][37] are more useful and can typically obtain information on processes acting faster than 100 ns.…”
Section: Introductionmentioning
confidence: 99%